Evaluation on Digital Online Videos-Project of Algebra Material - Rahmawati, Miftah Sigit; Kahar, Muhammad Syahrul; Fathurrahman, Muhammad (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
It's a challenges to learn algebra at the faculty of informatics in Sorong, Papua Barat, Indonesia. This suggested learning materials that were engaging and interactive and focused on practical skills. Algebra courses at times assign online digital video projects as a learning strategy. In this study, the skills of students in video-projects along with additional online, digital assignments pertaining to algebra were observed, examined, and determined. The ICSDR (Identify, Conceptualize/Connect, Storyboard, Develop, Review/Reflect, and Refine) methodology was utilized as the framework for a digital online video production. The ICSDR methodology makes algebraic content interactive for education and helps students in understanding the idea of online digital video projects. This study employed a hybrid approach, including project-based learning , descriptive theoretical-practical evaluation, and subjectively analysis. As a result, students are passionate about using applications for producing movies and working on assignments such as online digital video projects. This increased skills and experience in terms of video processing and video editing. Results from the subjective video evaluation were fairly good in terms of concepts, creativities, theories, and problem solving as practice questions. Keywords: e-learning, digital video, ICSDR, project-based learning